PENGARUH RISIKO PRODUKSI DAN HARGA KENTANG TERHADAP PERILAKU PRODUKSI RUMAHTANGGA PETANI DI KECAMATAN PANGALENGAN KABUPATEN BANDUNG (The Influence of Potato’s Price and Production Risk on Farm Household Production Behavior in Pangalengan Bandung) - Anna Fariyanti; Kuntjoro Kuntjoro; Sri Hartoyo; Arief Daryanto (Jurnal Agribisnis dan Ekonomi Pertanian, 2007)
The farm households face different risk on decision-making of resource allocation, especially production and price risk. The objectives of this paper are: (1) to analyze the effects of input allocation on the production risk, and (2) to analyze the influence of product price and production risk, incorporating the household economic behavior, especially on decision-making in resource allocation. Generalized autoregressive conditional heteroskedasticity (GARCH) model was used to analyze the production variance. The estimation of production function showed that the current production variance was influenced by the production variance of the previous period. Pesticide had a risk-reducing effect on the variance of production. On the contrary, land and nitrogen fertilizer had risk-inducing effect on the variance of production.